Analysis of Learning Material Quality and Teacher-Student Interaction on Learning Achievement and Student Satisfaction Level in Distance Education in Indonesia - Megavitry, Rissa; Salfin, Salfin; Akbar, Khoironi Fanana; Taryana, Taryana; Istiarsyah, Istiarsyah (The Eastasouth Journal of Learning and Educations, 2023)
Distance education in Indonesia has become a pivotal mode of learning, especially in the context of diverse geographical regions and the need for flexible educational opportunities. This study aims to analyze the impact of learning material quality and teacher-student interaction on learning achievement and student satisfaction levels in the Indonesian distance education landscape. A quantitative approach was employed to collect and analyze data from a diverse sample of distance education students. The study employed structural equation modeling (SEM) and various statistical tests to evaluate the relationships between key variables. The findings revealed strong relationships between learning material quality, student-teacher interaction, learning achievement, and student satisfaction levels. Notably, higher learning material quality was associated with improved learning achievement and student satisfaction. Positive student-teacher interactions also correlated with better learning achievement and increased student satisfaction levels. The results underscore the significance of investing in the quality of distance education materials and fostering positive interactions between students and teachers. These insights can inform educational policies and practices aimed at enhancing the distance education experience in Indonesia.